ISLAMIC EDUCATION PROBLEMS AND THEIR SOLUTIONS (QUALITY OF PAI TEACHERS) - Nurul Hidayah; Samsiadi Samsiadi; Mila Siscawati; Syamsurizal Yazid; Abdul Haris (Research and Development Journal of Education, 2022)
The reality of Islamic Religious Education is that many problems still occur in schools today. Islamic Religious Education is often considered a boring subject and learning activity. Many factors can cause this, including the unprofessionalism of a PAI teacher or students who are less enthusiastic about studying religious knowledge. So, this study aims to find the problems of Islamic education and its solutions, especially in the quality of Islamic Religious Education teachers. The research method used is library research. The research results are that currently, the teacher is the bearer of the educational mission whose job is to teach based on specific scientific and academic qualities. Then, get material rewards from the state and or other education management parties in which the compensation is not by the energy expended. Several solutions can encourage efforts to improve the problems of these educators, namely (1) increased teacher work discipline and implementation of good learned plans through coached, trained, and workshops. (2) the government and the foundation where teachers serve should pay attention to the welfare of teachers, (3) teachers should study and practice to improve their abilities (4) PAI teachers should be teachers who have met the qualifications